Induced Representations of Abelian Groups of Finite Rank - Tushev, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove that any irreducible faithful representation of an almost torsion-free Abelian group G of finite rank over a finitely generated field of characteristic zero is induced from an irreducible representation of a finitely generated subgroup of the group G.